An ecological trait matrix of Neotropical freshwater fishes - Albert, James S.; Abrahão, Vitor; Akin, Daniel R.; Allen, Jonathan G.; Ândrade, Marcelo; Arce, Mariangeles; Armbruster, Jonathan W.; Benine, Ricardo [UNESP]; Bernt, Maxwell J.; Bichuette, Maria E.; Birindelli, José; Bragança, Pedro; et al. (Springer Nature, 2025)
The Neotropical freshwater fish (NFF) fauna constitutes the most diverse continental vertebrate assemblage on Earth, with more than 6,345 species distributed across South America, Central America, and the Greater Antilles. These species display a bewildering array of ecophysiological and behavioral traits, or ecotraits, used to exploit habitat and food resources across geographical, climatic, and seasonal gradients. Despite intensive taxonomic and systematic studies, the literature on ecological preferences and tolerances of NFF species is scattered and incomplete, and we have previously lacked a centralized database. Here we present the first comprehensive dataset of ecotraits for the NFF fauna using published data and expert knowledge from the community of Neotropical ichthyologists. This ecomatrix includes adult modal values for 42 ecotraits scored for all valid NFF species, including body size, four of habitat utilization related to water chemistry, 21 of physical habitat structure, 10 of diet (i.e. trophic guilds), and six other behavioral traits. This ecomatrix is a foundation for future studies on the ecology and conservation of Neotropical aquatic biodiversity.